Literature Review: Faktor-Faktor yang Mempengaruhi Pengobatan Komplementer Alternatif (PKA) pada Pasien Hipertensi - Himmatul Khaira (Ameena Journal, 2025)
Education has been provided regarding routine and periodic medication. However, some patients still do not take their medication regularly and supplement it with complementary therapies, and some even skip medication altogether and use alternative treatments. Therefore, this study aims to identify factors influencing the use of complementary and alternative medicine in hypertensive patients. The article selection process for this literature review used a comprehensive search of five databases: EBSCO, Researchgate, Clinical Key, GARUDA, and PubMed to obtain quantitative research reports between 2020 and 2026. The article selection process applied the PRISMA model. Of the 397 articles found, 36 were screened, followed by 34 articles for eligibility. Factors identified in 10 of the 36 articles included religion, domicile, gender, marital status, education level, perception, motivation, level of knowledge about complementary and alternative medicine, beliefs, age, information sources, and drug side effects.